2019
DOI: 10.3390/en12244749
|View full text |Cite
|
Sign up to set email alerts
|

Global Climate Data Processing and Mapping of Degradation Mechanisms and Degradation Rates of PV Modules

Abstract: Photovoltaic (PV) systems are the cheapest source of electricity in sunny locations and nearly all European countries. However, the fast deployment of PV systems around the world is bringing uncertainty to the PV community in terms of the reliability and long-term performance of PV modules under different climatic stresses, such as irradiation, temperature changes, and humidity. Methodologies and models to estimate the annual degradation rates of PV modules have been studied in the past, yet, an evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 26 publications
(38 reference statements)
0
40
0
Order By: Relevance
“…Although out of the scope of the present work, in practice there are other important effects on the energy production and return on investment of PV installations, such as the higher degradation rate with increased module temperatures ( Ascencio-Vásquez et al, 2019 ; Vazquez et al, 2017 ) and the geographical and seasonal variations of soiling rates ( García et al, 2011 ; Sarver et al., 2013 ; Ilse et al., 2019 ), as well as other loss mechanisms at the module and system levels. When PV module temperatures are above a certain threshold, it becomes economically advantageous to turn trackers away from the sun, reducing the risk of damage and also the energy production.…”
Section: Discussionmentioning
confidence: 99%
“…Although out of the scope of the present work, in practice there are other important effects on the energy production and return on investment of PV installations, such as the higher degradation rate with increased module temperatures ( Ascencio-Vásquez et al, 2019 ; Vazquez et al, 2017 ) and the geographical and seasonal variations of soiling rates ( García et al, 2011 ; Sarver et al., 2013 ; Ilse et al., 2019 ), as well as other loss mechanisms at the module and system levels. When PV module temperatures are above a certain threshold, it becomes economically advantageous to turn trackers away from the sun, reducing the risk of damage and also the energy production.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of rainfall may vary from place to place. It was found that below 20 mm of rainfall, the PV surface was not adequately cleaned off in a dry California climate (based on the Köppen-Geiger climate classification) [67][68][69]. Light drizzle type rainfall enhanced dust adhesion on the module, which converted this dust into mud, which was hard to remove without any mechanical cleaning methods [70].…”
Section: Effect Of Rain and Moisturementioning
confidence: 99%
“…The spatially invariant inaccuracies of the underlying data set were therefore not addressed, as emphasis was instead put on the ML and DL models and their forecast accuracy, relative to the ERA5‐Land data. Furthermore, since the climate data used in the single‐WT forecasts concerns only a small geographical region, potential accuracy differences between distant data points [33] were avoided.…”
Section: Climate Datamentioning
confidence: 99%